The response of dissolved organic matter in different sedimentary regimes to nitrogen–phosphorus imbalanced input: insights from microcosm experiments - Yan Lan; Quan Chen; Min Wu; Danping Wu; Patryk Oleszczuk; Bo Pan (ENGINEERING Environment, 2026)

Spatial heterogeneity of biogenic VOC emissions and their potential contribution to secondary air pollution in three Chinese megacities: An exploratory assessment - Wen Dong; Danping Ma; Minghui Zhang; Xingbao Wang; Hanxing Zhou; Dongming Huang; Bo Yang; Xiaoai Jin; Jing Zhang; Yan Shi; Jian Chen; Yuan Ren (Urban Forestry & Urban Greening, 2026)

Identification of the methionine sulfoxide reductase (MSR) gene family in four Triticum species and functional analysis of TaMSRB5 involved in copper stress tolerance in Arabidopsis thaliana - Heng Chen; Luzhen Wang; Kexin Zhao; Shuai Yan; Yifei Chen; Lei Guo; Yinying Wu; Renmei Tian; Danping Li; Wenjia Zhang; Jianjun Liu; Haosheng Li; et al. (Plant Molecular Biology, 2026)

Correction: Synthesis, anti-tumor evaluation, and mechanistic investigation of 3-indolylpyrazole phenoxyacetamide derivatives against chronic myeloid leukemia cells - Mengting Liu; Guiyun Wu; Yue Zhou; Chengpeng Li; Danping Chen; Yan Li; Zhurui Li; Chenchen Li; Zhenchao Wang (Molecular Diversity, 2026)

Synthesis, anti-tumor evaluation, and mechanistic investigation of 3-indolylpyrazole phenoxyacetamide derivatives against chronic myeloid leukemia cells - Mengting Liu; Guiyun Wu; Yue Zhou; Chengpeng Li; Danping Chen; Yan Li; Zhurui Li; Chenchen Li; Zhenchao Wang (Molecular Diversity, 2026)

Subsurface structure assessment for landfill using distributed acoustic sensing: A case study in Qingdao, China - Shangrao Sun; Yizhe Su; Danping Cao; Hepu Chen; Kaijun Xu; Jian Tian; Houzhen Yan (Journal of Applied Geophysics, 2025)

Structural and (U-Th)/He thermochronological constraints on the Longmen Shan thrusting-gliding klippes, eastern margin of Tibetan Plateau - Xiaohan Lin; Danping Yan; Liang Qiu; Zhicheng Zhou; Huajie Song; Fei Kong; Chao Du (Science China Earth Sciences, 2025)

From benefit to burden: Assessing the full range of health impacts in urban green spaces using a threshold model - Bo Yang; Danping Ma; Xianting Wang; Wen Dong; Shengyu He; Yueting Zhou; Dubin Dong; Yan Shi; Yiping Wang; Songwei Zeng; Jian Chen; Jing Zhang; et al. (Journal of Environmental Management, 2025)

“Butterfly-effect” nano-platforms for cascade immune amplification and tumor clearance through multi-modal therapy and immune sensitization - Haoyu Chen; Xiaoying Kong; Jiahui Yan; Tianyi Wang; Yaqian Lv; Fenglang Zhang; Danping Liu; Yingshan Qu; Jun Fu; Wei Han; Jinsheng Shi (Chemical Engineering Journal, 2024)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Integrating data dependent and data independent non-target screening methods for monitoring emerging contaminants in the Pearl River of Guangdong Province, China - Rui Wang; Yanan Yan; He Liu; Yanxi Li; Meng Jin; Yuqing Li; RiZhu Tao; Qianghua Chen; Xuguang Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2023)

Novel flavan-3-ol-dithiothreitol conjugates derived from the degradation of grape seed proanthocyanidins and their neuroprotective potential - Meng Huang; Meng Li; Ying Zhang; Huan Gong; Yuju Zhou; Danping Zhu; Lingxi Li; Ning Ma; Yan Cui (Food Chemistry, 2023)

A climate perspective of the quasi-stationary front in southwestern China: structure, variation and impact - Danping Cai; Lingfeng Tao; Xiu-Qun Yang; Xiaozhuo Sang; Jiabei Fang; Xuguang Sun; Weiping Wang; Hongming Yan (Climate Dynamics, 2022)
Yunnan–Guizhou quasi-stationary front (YGQSF) is a unique weather phenomenon that frequently occurs during the winter half year over the Yunnan–Guizhou Plateau in southwestern China. Most of the previous studies analyzed it only with synoptic cases. This study investigates the structure, variation, and impact of this front from a climate perspective, using long-term high-resolution atmospheric reanalyses and high-density station records for 1981–2016. An objective method quantifying YGQSF is proposed and three indexes are defined to measure its intensity, frequency, and location, respectively, with horizontal gradient of air potential temperature at a terrain-following level of sigma 0.995. With these indexes, climatological structure, subseasonal variability as well as climatic impact of the front are comprehensively examined. In climatology, YGQSF as a north–south-oriented low-level front is found to occur the most frequently during January–February–March, determined predominately by the coldness from the east of the front. The structure of the front identified essentially reflects an obstruction of high-terrain Yunnan (the western part of the plateau) to the low-level cold air mass, which makes near-surface cold northeasterly winds cease westward intruding and veer upward over relatively low-terrain Guizhou, transporting moisture upward and forming low clouds. A sharp climate contrast is thus formed between two sides of the front: cold, sunless, and continuously rainy Guizhou versus warm and sunny Yunnan. Furthermore, the front features significant subseasonal variations with periods at around 30 days and 60 days largely in its intensity. Anomalously strong YGQSF events which are caused 75% by the cold anomaly from the east but no more than 17% by the warm anomaly from the west yield different anomalous structures, but consistently amplify the sharp climate contrast between Yunnan and Guizhou.

Association Between the Blood Copper-Zinc (Cu/Zn) Ratio and Anemia in Patients Undergoing Maintenance Hemodialysis - Sujun Zuo; Mengmeng Liu; Yun Liu; Shilin Xu; Xiaoshi Zhong; Jingxian Qiu; Danping Qin; Rongshao Tan; Yan Liu (Biological Trace Element Research, 2022)

Structural styles and tectonic evolution of Cretaceous to Cenozoic faults in the Linhe Depression of Hetao Basin, China: implications for petroleum traps - Zhicheng Zhou; Wenlong Ding; Ruifeng Zhang; Danping Yan; Baocheng Jiao; Chenlin Wu; Tianshun Liu; Xiaoyu Du; Mingwang Xue (International Journal of Earth Sciences, 2021)

Enzymatic cascade systems for D-amino acid synthesis: progress and perspectives - Anwen Fan; Jiarui Li; Yangqing Yu; Danping Zhang; Yao Nie; Yan Xu (Systems Microbiology and Biomanufacturing, 2021)

Lower Levels of Blood Zinc Associated with Intradialytic Hypertension in Maintenance Hemodialysis Patients - Yun Liu; Yuanyuan Zheng; Liangtao Wang; Xiaoshi Zhong; Danping Qin; Wenxuan Chen; Rongshao Tan; Yan Liu (Biological Trace Element Research, 2021)
Intradialytic hypertension (iHTN) has been related with an increased risk of mortality, with imbalances in trace elements being frequent in maintenance hemodialysis (MHD) patients. The aim of this study was to analyze the relationships between the levels of blood trace elements and iHTN in MHD patients. A total of 144 MHD patients were enrolled in September, 2019 (66 females; 5616 hemodialysis treatments), with a mean age of 64.33 ± 13.39 years and median vintage of 33.50 (16.25–57.50) months. Patients exhibited an average peridialytic systolic blood pressure (SBP) change of − 4.18 ± 20.22 mm Hg in the next 3 months. Thirty-four (23.6%) patients had persistent iHTN (piHTN). These patients were characterized by older age, higher rate of hypozincemia, and modified Charlson comorbidity score, whereas lower blood zinc and hemoglobin, at the time of their recruitment. No significant difference in the levels of other blood trace elements was observed between groups. A general linear mixed (GLM) model showed that with every mg/L point lower mean blood zinc at baseline, the peridialytic SBP change was increased by 4.524 mm Hg ( P < 0.001). Binary logistic model in modulate of the GLM model revealed that the lower level of blood zinc was associated with piHTN (OR = 0.433, 95 % CI 0.295 to 0.637, P < 0.001). Multivariate analysis confirmed both above results. Our study indicated that lower blood zinc was independently associated with piHTN in patients undergoing MHD, but prospective studies with larger population are still needed.

Early Cretaceous Post-Collisional Collapse of the Yidun Terrane: Geochronological and Geochemical Constraints from Calc-alkaline to Alkaline Basalts in Xiqiu Area, Southwest China - Xutuo Li; Danping Yan; Liang Qiu (Journal of Earth Science, 2018)

ATP7B Mutation Detection and Pathogenicity Analysis: One Atypical Case of Wilson’s Disease with Adrenocortical Insufficiency - Min Liu; Meifang Jin; Xuqin Chen; Bo Wan; Yue Guo; Mao Sheng; Linqi Chen; Lei Zhao; Danping Huang; Yan Li (Journal of Molecular Neuroscience, 2018)